Analysis of the Impact of Payroll Accounting and Service Charge on the Work Commitment of PT Samaja Bali Villas Employees - I Made Samjaya RAJISTHA; Ni Putu RIASNING; Ni Made Vita INDRIYANI (Loka: Journal Of Environmental Sciences, 2024)
Purpose:This study is entitled "Analysis of the Impact of Payroll Accounting and Service Charges on the Work Commitment of Employees at PT. Samaja Bali Villas." The problem discussed in this study is the implementation of work standards based on employee departments that must be met to achieve company goals. This gives rise to different views regarding financial compensation, making the company uncertain about employee perceptions regarding compensation. This study aims to prove whether payroll accounting and service charges influence employee work commitment.Methodology:This study was conducted at PT. Samaja Bali Villas, located at Jl. Kunti II No. 18, Seminyak. The study population included 31 employees of PT. Samaja Bali Villas uses a simple random sampling method. The data analysis technique used was descriptive analysis.Findings:The results achieved in this study are: (1) Payroll accounting at PT. Samaja Bali Villas is considered good and effective, with what employees receive based on their contracts. (2) Service charges at PT. Samaja Bali Villas certainly follow existing government regulations, so that it is effective and efficient in increasing employee work commitment.Implication:This study has implications, namely, the aim of determining the impact of Payroll Accounting and Service Charge on the work commitment of PT. Samaja Bali Villas employees.